Analysis of High School Students' Errors in Solving Story Problems on Systems of Linear Equations with Three Variables - Darmayanti, Selvina; Shanty, Yustika Laras; Angraini, Lilis Marina (EDUPEDIA Publisher, 2024)
This research is motivated by the large number of students who make mistakes when working on questions, so it can be an indication of how well students understand the material. SPLTV material was chosen for this research because SPLTV has components that students must understand so that they can easily determine mistakes made by students. This research aims to reveal the facts, circumstances, phenomena, variables and circumstances that occurred when the research was conducted. This type of research is qualitative research with a quantitative descriptive approach. The research subjects were 34 class X students at SMAN 2 Tualang. The data collection techniques used in this research are: 1) written tests, and 2) interviews. Based on the results of data analysis, a conclusion was obtained which showed that students made mistakes in Newman's stages, namely: errors in reading were 23.53%, which means that the majority of students read the question instructions well. The large percentage of students making errors in understanding is 91.18%, and students making transformation errors with a percentage of 55.88%. In process skill errors, the number of students who made mistakes was 82.35%, and 88.23% of students made mistakes in writing/notation. Factors that cause errors include: not being careful, not being able to read the question, not understanding the problem, and not being able to carry out the procedures or steps that will be used to solve the question.